Palmitic acid acutely stimulates glucose uptake via activation of Akt and ERK1/2 in skeletal muscle cells[S] - Jing Pu; Gong Peng; Linghai Li; Huimin Na; Yanbo Liu; Pingsheng Liu (Journal of Lipid Research, 2011)
Abstract Chronic exposure to saturated fatty acids can cause insulin resistance. However, the acute effects of fatty acids are not clear and need to be elucidated because plasma fatty acid concentrations fluctuate postprandially. Here, we present the acute effects of palmitate (PA) on skeletal muscle cells and their underlying molecular mechanisms. Immunofluorescence results showed that PA rapidly induced GLUT4 translocation and stimulated glucose uptake in rat skeletal muscle cell line L6. Phosphorylation of AMP-activated protein kinase (AMPK), Akt, and extracellular signal-related kinase1/2 (ERK1/2) was enhanced by PA in a time-dependent manner. Cell surface-bound PA was sufficient to stimulate Akt phosphorylation. The inhibitors of PI3 kinase (PI3K), AMPK, Akt, and ERK1/2 could decrease PA-induced glucose uptake, and PI3K inhibitor decreased AMPK, Akt, and ERK1/2 phosphorylation. Weakening AMPK activity reduced phosphorylation of Akt but not ERK1/2, and Akt inhibitor could not affect ERK1/2 activation either. Meanwhile, ERK1/2 inhibitors had no effect on Akt phosphorylation. Taken together, our data suggest that PA-mediated glucose uptake in skeletal muscle cells may be stimulated by the binding of PA to cell surface and followed by PI3K/AMPK/Akt and PI3K/ERK1/2 pathways independently.